IMPROVING SMALL AND MEDIUM BUSINESS INNOVATION KNOWLEDGE TRANSFER THROUGH TRIPLE HELIX AGENTS - Dewandaru, Bothy; Rahmadi, Afif Nur; Sudjiono, Sudjiono (Perpustakaan dan Penerbitan Unismuh Makassar, 2021)
Innovative developments in various countries are based on the triple helix mode. The triple helix model can play an important role in solving small and medium enterprise development problems. This model can also reveal the potential benefits and benefits for creative SMEs in developing countries. The purpose of this study was to determine the effect of knowledge transfer by academia, industry and government on SME innovation. This type of research is quantitative research with a total sample of 67 tofu and ikat weaving craftsmen in Kediri City. The results of this study are that there is a positive influence of knowledge transfer by industry on SME innovation, there is a positive influence of knowledge transfer by the government on SME innovation and there is no effect of knowledge transfer by academics on SME innovation.